Active disturbance rejection controller for variable flow gain–proportional throttle cartridge valve. (November 2016) - Yao, Jing; Zhang, Yang; Yu, Bin; Cao, Xiaoming; Zhao, Jinsong
The proportional throttle cartridge valve has been widely used in heavy machine due to its fast response and huge flow rate. However, large flow impact could occur at the instant of proportional throttle cartridge valve opening, which is harmful to system stability and service life of machines. A variable flow gain–proportional throttle cartridge valve was proposed in this study to reduce the vibration of hydraulic drive system caused by the flow impact. Nevertheless, the variable flow gain introduced a strong nonlinearity, as well as a big flow force disturbance, a friction force disturbance, a flow–pressure nonlinear relationship, and a variable load stiffness which are challenges for high accurate control of spool position. Therefore, a third-order active disturbance rejection controller was developed to enhance the antidisturbance ability and improve the control precision of the variable flow gain–proportional throttle cartridge valve as well. First, the mathematical model of the variable flow gain–proportional throttle cartridge valve was established by identification of system parameters. Second, the active disturbance rejection controller was designed, and its parameters were tuned in simulation environment. And third, relevant experiments on a DN80 variable flow gain–proportional throttle cartridge valve test system were conducted to validate the proposed control strategy. The experimental results approved that compared with the well-tuned proportional–integral–derivative controller, the response time and the overshoot were almost cut to half, and the hysteresis error decreased by 75% using active disturbance rejection controller. The experiment results also indicated that variable flow gain–proportional throttle cartridge valve with active disturbance rejection controller increased the robustness of the variable flow gain–proportional throttle cartridge valve in the presence of nonlinear and uncertain disturbance and improved the control precision and dynamic response greatly.